BLENDED LEARNING MEMBANTU MAHASISWA KEBIDANAN BELAJAR ASUHAN PERSALINAN KALA IV - Dwi Ghita (Stikes Graha Edukasi Makassar, 2022)
Health learning media that can easily increase one's knowledge. In the modern era, the use of technology is growing very rapidly through the internet network. Facilitating students to study independently and can be accessed efficiently anywhere and anytime. Stage IV labor is a vulnerable period in the delivery process so that management skills are very important. The purpose of this study was to produce learning media for android-based health students in improving the skills of midwifery students. The method in this study used a combined method research design, namely Research and Development (R & D) and Pre-experiment (one group pre-test and post-test design). Educational media are developed and validated using R & D (Research and Development) developed by Borg and Gall